Human development - Crandell, Thomas L.; Crandell, Corinne Haines; Vander Zanden, James Wilfrid (New York McGraw-Hill Higher Education, 2009)
The study of human development; Beginnings; Birth and infancy: the first two years; Early childhood: 2 to 6; Middle childhood: 7 to 12; Adolescence; Early adulthood; Middle adulthood; Late adulthood; The end of life.
Keywords: Developmental psychology -- Textbooks; Tâm lý học